Wheels : a pictorial history - Tunis, Edwin, 1897-1973. (New York : Crowell, 1977)
Traces man's development and use of the wheel from the Elamite chariot of 2,500 B.C. to the transcontinental buses of today.
Keywords: Carriages and carts -- History -- Juvenile literature; Automobiles -- History -- Juvenile literature; Wheels; Vehicles -- History; Carriages and carts -- History; Automobiles -- History